Impact of screen use on young children's development: a review of research and recommendation - Mączyńska, Wiktoria; Dutkiewicz, Justyna; Wijata, Michał; Wijata, Anna; Przybyłek-Stępień, Zuzanna; Bartosiński, Ryszard; Szustak, Jan; Kąpa, Maria; Szepietowski, Bartosz; Kaźmierczak, Jakub; Rycerz, Ewelina; Pasek, Piotr (Journal of Education, Health and Sport, 2025)
Introduction: The modern world is characterized by widespread access to digital devices, leading to increasing use by children in the earliest years of life, affecting their development in various spheres of life. Aim of the Study: The purpose of the work is to analyze the impact of excessive use of digital technologies on the development of young children, with a focus on cognitive, emotional, social and physical aspects. Also, it aims to provide recommendations for healthy management of time in front of the screen and to promote activities that support the comprehensive development of children. Materials and Methods: The paper is a review and is based on an analysis of scientific articles, reports and guidelines from international organizations (e.g. WHO, UNICEF), focusing on publications from 2010-2023. Databases such as PubMed, Scopus and Google Scholar were used to search for relevant materials. Conclusions: The results indicate that excessive use of screens can negatively affect language development, attention, cognitive abilities and emotion regulation. On the other hand, appropriately selected educational content and moderated time spent in front of a screen can support cognitive development. An analysis of the literature has also shown that exposure to digital devices can limit social interactions with parents and peers, which is crucial for the formation of social skills. In addition, studies point to their physical consequences such as vision problems, sleep disturbances and reduced physical activity. The paper emphasizes the importance of an informed and responsible approach to the use of technology in raising children. Recommendations are made for parents and caregivers to limit time in front of screens, choose appropriate content and promote healthy habits. Conclusions are also made about the need for further research, especially long-term research that will help better understand the effects of digital device use on the development of young children.